PENGARUH KEPEMILIKAN MANAJERIAL, KEBIJAKAN HUTANG, PROFITABILITAS, UKURAN PERUSAHAAN DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2011-2013 - Juliana -; Azwir Nasir; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research were to analyze the influence of managerial ownership, debt policy, profitability, firm size and investment opportunity set on dividend policy on manufacturing company listed in Indonesia Stock Exchange for period 2011 until 2013. This study used purposive sampling technique and the final sample that has chosen is 16 manufacturing companies listed on Indonesia Stock Exchange. Analysis technique of the data used was multiple linier regression with SPSS. The result of this research, shows that managerial ownership, debt policy, profitability, firm size and investment opportunity set have positive and significant influence on dividend policy on manufacturing company listed in Indonesian stock exchage. Partially, managerial ownership, debt policy and profitability have positive and significant influence on dividend policy, but firm size and investment opportunity set have no effect on dividend policy. The influence of managerial ownership, debt policy, profitability, firm size and investment opportunity set are about 25.3% and 74.7% are impacted by other variables.Keywords: Managerial Ownership, Debt Policy, Profitability, Firm Size, Investment Opportunity Set, Dividend Policy.